Implementasi Model Machine Learning dalam Mengklasifikasi Kualitas Air - Stacyana Jesika; Suci Ramadhani; Yohanna Permata Putri (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Water quality is an important factor in maintaining human health and environmental sustainability. Water pollution is a major problem in Indonesia, so it is important to monitor and classify water quality effectively. Implementation of machine learning models in classifying water quality can provide important benefits in the environmental and health fields. This research uses two machine learning algorithms, namely KNN and SVM, to classify water quality. The water quality data used comes from the website www.kaggle.com, which was uploaded by MsSmartyPants in 2021 with the title "Water Quality (Dataset for water quality classification)". Implementation of this machine learning model involves the steps of data collection, data pre-processing, selection of relevant attributes, algorithm selection, model training, evaluation, and model implementation for real-time water quality classification.